Synthesis of robust and multifunctional microcapsules for protective coatings used in marine and offshore environments - Sun, Dawei (2017)
During service, anticorrosion coatings in seawater are susceptible to wear and scratched damages resulting in the re-exposure of steel substrates. Smart coatings are prepared by formulating microcapsules in polymeric coatings, where healing agents can be released to seal scratches or as lubricant to mitigate wear damages after the microcapsules are broken. Among these microcapsules, isocyanates-loaded microcapsules attracted increasing attentions due to easy operation. However, short service life in moist environments, poor stability in organic solvents and weak mechanical strength of microcapsules restrict their further applications. Therefore, further development of robust microcapsules is of great importance. 4,4’-methylenebis (cyclohexyl isocyanate) (HMDI) was encapsulated successfully in water resistant microcapsules by combining interfacial polymerization and modified in situ polymerization in an oil-in-water emulsion system. The water resistant microcapsules were characterized through various analytical methods, and the influence of agitation rate on diameters, shell thickness and core fraction of microcapsules were investigated systematically. The relative residue of core fraction was higher than 80% after 20 days in moist environments including ambient water, open air, warm water, acidic and alkaline aqueous solutions. However, water resistant microcapsules resist poorly to organic solvents. In addition, HMDI was also encapsulated successfully in double resistant microcapsules possessing superior stability in both aqueous solutions and organic solvents. Besides outstanding stability in aqueous solutions, double resistant microcapsules also possess outstanding stability in organic solvents. The relative residue of core fractions was beyond 90% after 30 days in ambient hexane, xylene and ethyl acetate, respectively. The influences of parameters including microcapsule size, concentration and immersion duration on the stability of double resistant microcapsules in organic solvents were investigated systematically. However, double resistant microcapsules possess poor stability in acetone and weak mechanical strength. In order to improve shell strength and acetone resistance of resultant microcapsules, another layer of metal shell was covered on double resistant microcapsules as trifunctional microcapsules. The trifunctional microcapsules were characterized systematically, presenting superior stability in acetone, and higher mechanical strength than that of double resistant microcapsules. In order to investigate the influence of metal shell on microcapsules, systematic comparison was conducted between double resistant microcapsules and trifunctional microcapsules. The trifunctional microcapsules possess shell strength several times higher than that of double resistant microcapsules. Even in polymeric matrix, the multifunctional composite coatings containing trifunctional microcapsules also possess higher compressive strength and compressive modulus than those containing double resistant microcapsules. Self-healing samples and self-lubricating samples were fabricated successfully by dispersing two types of microcapsules in epoxy resin. Both double resistant microcapsules and trifunctional microcapsules showed superior self-healing anticorrosion performance towards steel panels. However, trifunctional microcapsules possess marginal self-lubricating performances in epoxy resin due to the existence of metals shell, comparing with outstanding self-lubricating performance of double resistant microcapsules. Robust microcapsules were fabricated successfully through various encapsulation techniques. However, further investigations are still needed to improve the shortages of current microcapsules.